TRANSBOUNDARY WATER MANAGEMENT IN THE EUPHRATES-TIGRIS BASIN: DYNAMICS OF REGIONAL COOPERATION, SUSTAINABILITY AND GOVERNANCE - (:unkn) unknown (SPRINGER, 2009)
Since the late 1980s, numerous academic studies and non-academic popular writings have argued that the Euphrates-Tigris Basin is one of the transboundary river systems in the Middle East where conflicts would break out due to water scarcity, degradation of water quality and competing water-based socio-economic development policies of the riparian states, namely Turkey, Syria and Iraq. On the one hand, various incidents have occurred since 1970s that have caused tensions among the riparian states. On the other hand, however, the crises and deadlocks in the hydropolitical relations of the co-riparians have also paved the way for various cooperation efforts and initiatives regarding the utilization of the Euphrates-Tigris waters. This study analyzes those efforts and initiatives, as well as various aspects of sustainable water resource management and governance practices that can act as tools for preventing future disputes among the co-riparians in the future.
Keywords: Euphrates; Tigris; regional cooperation; Joint Technical Committee; Three Staged Plan; sustainable water resource management; water governance